PERAN ORGANISASI ICMI PADA MASA AWAL ERA REFORMASI - Azra Afifatuzahra (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2024)
It is felt that the dynamics of ICMI's existence with all its advantages still do not make a definite contribution to the progress and development of the Indonesian nation and Muslims. This is where it is important to remember the role of ICMI in the early days of the reform era because many people gave positive responses from the community, because of this ICMI in Indonesia has the potential to give birth to various new thoughts that can provide renewal and progress for Muslims in this era. That. The method used in this historical research involves analysis of historical documents, archives and relevant literature to trace the development of ICMI during the early Reform Era. This research involved text analysis of ICMI speeches, articles and publications as well as relevant historical documentation. This approach involves an in-depth study of ICMI's specific role in one or several important cases during the early period of the Reformation in the form of participation in demonstrations, contributions to the political process, or role in facilitating inter-religious dialogue. This research found that since ICMI was officially founded, this organization has always received enormous support from the government. In fact, during the post-Soeharto regime change, ICMI always played a role in politics. Therefore, at this time ICMI has become a force to be reckoned with in national politics. But it is not uncommon for ICMI to become a target for political figures to gain power. In the reform era there were many changes in political interests such as how to become president, governor, minister, regent, member of the council. Despite this, Muslim intellectuals continue to show their enthusiasm, even though their voices no longer resonate so much in national politics. Keywords: ICMI, Reform Era